Leadership in the public sector: A meta-analysis of styles, outcomes, contexts, and methods - Leonie Backhaus; Rick Vogel (Public Administration Review, 2022)
Leadership has attracted growing attention among scholars and practitioners in public administration. With the rising availability of study results, however, it becomes increasingly difficult to keep track under which conditions leadership does or does not make a difference in the public sector. This study provides a meta-analysis of administrative leadership and various correlates that research has theorized as outcomes of leadership. The results of a multi-level random-effects meta-analysis based on 486 effect sizes from 151 studies show that correlations are stronger for the achievement of beneficial than for the prevention of detrimental outcomes, as well as for group- and organization-related than for employee-related outcomes. Moderation analyses reveal that leadership style, administrative tradition, administrative subfield, and methodological factors explain heterogeneity in effect sizes.
Keywords: 340